ANTECEDENTS OF BRAND EQUITY - Andina Seliani; Luki Adiati Pratomo (Universitas muhammadiyah malang, 2019)
This study intends to examine the effects of brand association, brand loyalty, brand awareness, brand image, and country-of-origin image on brand equity in Zara, Pull and Bear, H&M, and Uniqlo brands. To collect samples, a non-probability method was utilized with a purposive sampling technique, and obtained 135 respondents who were social media users and have bought Zara, Pull and Bear, H&M, and Uniqlo brands in the past one year. The analytical tool used was Multiple Regression. The results showed that there were positive influences among brand association, brand loyalty, brand awareness, brand image, and country-of-origin image on brand equity.